Dampak Program Kota Tanpa Kumuh terhadap Perkembangan Industri Kecil Mikro, Koperasi, dan Hotel di Lokasi Kumuh - Rijal, Muhammad Khoirur (UI Scholars Hub, 2025)
Abstract The development of a region is frequently followed by the emergence of slum settlements which further obstruct the growth of productive activities. This study evaluates the effects of Slum Upgrading Program in Indonesia to the growth of small-micro industries, cooperatives, and hotels in slum area. By using difference in difference (DID) method, this study analysed 3427 villages in 33 provinces during 2016-2018. It was found that program increased the number of micro and small industries and hotels, and reduced the number of cooperatives. This finding indicated that mitigate slums effectively have an impact on the development of small industries and tourism facilities.